Merry Pinkmas! - Kann, Victoria; Kann, Victoria (New York Harper Festival, 2014)
This year Pinkalicious has decided she wants a bright pink artificial Christmas tree. But Mommy and Daddy immediately say no -- the Pinkertons always get real trees for the holidays. Despite Pinkalicious's begging and pleading, each family member has a different objection: real trees smell better; it's tradition; and there is definitely no room to store a big pink tree in the house after Christmas! Pinkalicious is disappointed, but she tries to put on her best cheerful face. Then, the day before Christmas, Mommy and Daddy surprise Pinkalicious by coming home with a gorgeously pink artificial tree and Pinkalicious is delighted! It's pinkatastic!
"Based on the HarperCollins book Pinkalicious"
101913
Keywords: Christmas stories; Pink; Color; Fiction; Juvenile works